Leadership Training for Inclusive Village Women - Pranata, Andi; Ramdhani, Suci; Yasa, I Putu Buda; Al Farisi, Moh. Salman; Nurfidah, Nurfidah; Fandir, A.; Rahmatika, Qais Ainu; Auliya, Indana Zahratul (Abdi Masyarakat, 2024)
Inclusive Village Women's Leadership Training aims to increase women's leadership capacity at the village level with an approach based on gender equality and inclusive development. This training involved 40 female participants from various villages in diverse areas, with a focus on empowering women through strengthening knowledge and skills in leadership, decision making and managing village resources. The methods used in this training include theoretical lectures, participatory discussions, simulations and role playing, case studies, and field experiences, all of which are designed to hone participants' practical skills in facing leadership challenges in their villages. The results of the training implementation showed a significant increase in participants' understanding of the concepts of inclusive leadership, gender equality and women's empowerment. Post-training evaluations also showed that most participants felt more confident in taking on leadership roles and playing an active role in decision making in their villages. However, challenges in implementing this training include knowledge gaps between participants, limited access to technology in some villages, and the need to strengthen more specific material according to the local context. Overall, this training was successful in providing a strong foundation for women to lead inclusively, but requires ongoing monitoring to ensure effective implementation at the village level.